USING OF THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY IN THE ACCEPTANCE OF MOBILE BANKING APPS - Lukman, Hendro; Imelda, Elsa; Vianney, Vannessa Maria; Darwis, Andrea Stephanie; Pratama, Go Cecilia Claudia (International Journal of Application on Economics and Business, 2025)
Current technological developments are also felt in personal financial activities. Personal financial activities will be related to banking business services. One of the impacts of implementing technology for personal financial activities is the Mobile Banking Application (Apps -M Banking). The research to analyzes the acceptance of Apps. M-Banking by customers. The analysis uses the Unified Theory of Acceptance and Use of Technology approach. This study is descriptive quantitative using primary data. Data collection using digital questionnaires with convenience and snowball methods. The data collected were 75 respondents. The analysis used Structural Equation Modeling with Performance Expectancy, Efficient Expectancy, Social Influence and Facility Condition as independent variables. The results of this study indicate the Performance Expectancy, Social Environment do not affect the Use Behavior of bank customers in using Apps. M-Banking through Behavioral Intention. While Effort Expectancy and Facility Condition affect Use Behavior using the Mobile Banking application through Behavioral Intention. The conclusion of this study shows that App. Conventional bank M-Banking has not fully met customer expectations so that the social environment does not affect it even though easy use and support facilities already support it. This study provides input for banks to improve the M-Banking App to further improve customer performance.